The role of the aminoacetone pathway on lactic acidemia of iron-deficiency anemia - Villalobos, Annabelle
Studies on the metabolic effects of iron-deficiency anemia on lactic acidemia in male albino rats of the Sprague Dawley strain were done. Methylglyoxal synthetase which synthesizes methylglyoxal from dihydroxyacetone phosphate was found absent in the liver, heart, and diaphragm muscle of normal rats. However, the activity of glyoxalase which synthesizes lactic acids from methylglyoxal is increased in the liver and diaphragm muscle of iron-deficient rats. On the other hand, mythlglyoxal concentration in the liver, diaphragm and blood was found to be lowered which suggested active turnover of this compound in iron-deficiency anemia. Glycine injected intraperitoneally resulted in market lactic acidemia which was found to peak after 2 hours. Similar injection of aminoacetone caused a more severe lactic acidemia that peaked earlier at one hour. Approximately 50% of the lactic acid in the iron-deficient rats was found to be the D(-) isomer. These findings are compatible with a very active amino-acetone pathway. Glycine levels in serum was found to be increased in the anemic rats indicating a derangement in the metabolism of this amino acid. Studies on human plasma from anemic lactating mother showed a similar marked increase in the glycine level, total lactic acid, and D(-) lactic acid.